RoboStudio: A visual programming environment for rapid authoring and customization of complex services on a personal service robot - Datta, C.; Jayawardena, C.; Kuo, I. H.; MacDonald, B. A. (2012 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2012)
Service robots for personal and domestic use are increasingly gaining momentum. Easy and efficient programming of such robots is an enormous research and commercial space that is beginning to be explored. In this paper, we present RoboStudio, a Visual Programming Environment (VPE) to program the interactive behavior of personal service robots. RoboStudio lies at the intersection of VPEs which aid in authoring the robot user interface and control logic. A novel contribution of this work is that it advances the research in authoring service applications on robotic platforms, specially for researchers who do development in decentralized multidisciplinary teams and validate their research goals through field trials. Furthermore, service robot programming environments is a novel area of research, particularly when it comes to expressing what the robot does in a declarative syntax.